Pemberdayaan Kelompok Wanita Tani (KWT) Berkah Tani 2 Desa Ngasem dalam Pembuatan Hidroton sebagai Upaya Pengolahan Limbah Organik - Agustina, Putri; Agustina, Lina; Astuti, Rina; Santhyami; Kusumadani, Annur Indra; Sari, Siti Kartika (Cattleya Darmaya Fortuna, 2025)
The community service activity partner is KWT Berkah Tani 2 Ngasem Village, Central Java. KWT Berkah Tani 2 and the surrounding community already have a place to cultivate plants and, in this area, they produce a lot of organic waste per day, not all of the organic waste produced is utilized. Therefore, the aim of this service is to provide education about hydrotone compost to KWT Berkah Tani 2. We introduced an innovation, especially in utilizing organic waste into compost as a mixture of hydrotone. The solution offered is developing environmentally based education at KWT Berkah Tani 2 by holding educational activities on making compost hydrotone for the Ngasem village community. Service activities are carried out in four phases using socialization, practice and application methods. The four phases are socialization and preparation, preparation of tools and materials, implementation of activities (making hydrotone compost and application to plants) as well as coaching and supervision. Hydrotone is not only an innovative solution in waste management, but has also been proven to increase environmentally friendly agricultural efficiency.